Acceleration of the thrombin inactivation of single chain urokinase-type plasminogen activator (pro-urokinase) by thrombomodulin. - de Munk, G A (1991)
The in vitro effects of thrombomodulin on the inactivation of single chain urokinase-type plasminogen activator (scu-PA) by thrombin were investigated by incubating scu-PA with varying concentrations of human thrombin, in both the absence and presence of soluble rabbit thrombomodulin. 50% inactivation of scu-PA occurred in 45 min at 160 ng/ml thrombin in the absence of thrombomodulin and at 4.6 ng/ml thrombin in the presence of thrombomodulin. No difference was found in either the absence or the presence of thrombomodulin between the inactivation rates of high molecular weight scu-PA, and a low molecular weight scu-PA which lacked the growth factor and kringle domains. Enzyme kinetic experiments with varying concentrations of scu-PA showed that thrombomodulin decreased the Km of thrombin for scu-PA from 7.8 to 0.43 microM and increased the kcat from 0.30 to 1.2 s-1, corresponding to a 70-fold increase in the second-order rate constant kcat/Km. SDS-polyacrylamide gel electrophoresis showed that scu-PA was cleaved into two chains upon inactivation by thrombin, and confirmed the acceleration effect of thrombomodulin on inactivation of scu-PA. Thrombomodulin thus not only has anticoagulant properties but is also antifibrinolytic. The acceleration may imply a new mechanism for the regulation of local plasminogen activator activity on the cell surface.